2023
DOI: 10.1002/mp.16715
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal frequency domain analysis for blood velocity measurement during embolization procedures

Martin G. Wagner,
Joseph F. Whitehead,
Sarvesh Periyasamy
et al.

Abstract: BackgroundCurrently, determining procedural endpoints and treatment efficacy of vascular interventions is largely qualitative and relies on subjective visual assessment of digital subtraction angiography (DSA) images leading to large interobserver variabilities and poor reproducibility. Quantitative metrics such as the residual blood velocity in embolized vessel branches could help establish objective and reproducible endpoints. Recently, velocity quantification techniques based on a contrast enhanced X‐ray se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…49 As these frequency ranges do not overlap, the influence of contrast changes caused by respiratory motion on the blood velocity analysis conducted in the spatiotemporal frequency domain is reduced. These results further confirm the findings of Wagner et al 33 where no significant difference was found between blood velocity measurements performed on DSA images and images with no background subtraction.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…49 As these frequency ranges do not overlap, the influence of contrast changes caused by respiratory motion on the blood velocity analysis conducted in the spatiotemporal frequency domain is reduced. These results further confirm the findings of Wagner et al 33 where no significant difference was found between blood velocity measurements performed on DSA images and images with no background subtraction.…”
Section: Discussionsupporting
confidence: 92%
“…Among the various qDSA techniques reported, [31][32][33] the velocity quantification algorithm proposed by Wagner et al 33 was used throughout this study. This algorithm was preferred due to its global, non-iterative approach for blood velocity quantification from a TAM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations